Characterization of the five-tier model of creative mathematical thinking in primary school learners - Susilowati, Ervita Tri; Prayitno, Anton; Baidawi, Muhammad (Fakultas Tarbiyah Universitas Ibrahimy, 2025)
Creative mathematical thinking skills among elementary students remain relatively low, largely due to predominantly procedural instruction, highlighting the need to examine the characteristics of their innovative thinking stages in solving data processing problems using the Subanji five-stage model. The study aimed to identify and describe students’ creative thinking patterns in handling ordinal data through the stages of pre-imitation, imitation, modification, combination, and construction. Employing a qualitative case study approach, data were collected from 38 fifth-grade students in Malang through open-ended tasks, think-aloud protocols, interviews, and documentation. The analysis involved data reduction and triangulation. Results revealed the distribution of students across stages: 10.53% at pre-imitation, 34.21% imitation, 23.68% modification, 18.42% combination, and 13.16% construction. Students showed a progression from routine and imitative approaches to independently constructed strategies, such as assigning weighted scores to ranked data and analyzing the frequency of options. These findings suggest that the Subanji model effectively captures the development of creative mathematical thinking and support the integration of open-ended tasks and scaffolded guidance to foster creativity in mathematics learning.